THE CORRELATION BETWEEN PLAYING INTENSITY OF ONLINE GAME AND ENGLISH VOCABULARY MASTERY IN SMPN 7 SINJAI - A. Nur Wafiq Azizah; Nurdin Noni; Sultan Baa (State University of Makassar, 2023)
This study aims to determine the relationship between the intensity of playing online games and students' vocabulary mastery and student opinions regarding the use of online games in learning English vocabulary. This study used a mixed-method research design. Data collection in this study was conducted by conducting vocabulary tests for 30 students and interviewing 6 students from SMPN 7 Sinjai. The results of the study showed that there was a correlation between playing online games with students' vocabulary mastery and their perception of the use of online games in learning English vocabulary where students say that through online games, they are helped in mastering English vocabulary and broaden their vocabulary horizons where in this case students indirectly practice learning methods while playing.Keywords— online game, correlation, and perception of students.